International adoption of the Second Step program: Moderating variables in treatment effects - Moy, Gregory; Polanin, Joshua R.; McPherson, Casey; Phan, Thuy-Vy (School Psychology International, 2018)
Second Step is a universal social-emotional learning program designed to decrease antisocial behaviors, increase prosocial behaviors, and increase knowledge about content curriculum. Given the international focus of using Second Step to improve social-emotional skills, it is especially important to provide an updated synthesis on the effect of the intervention. A single-program meta-analysis was completed in order to determine effects of participating in Second Step and to explore moderators of program effectiveness on prosocial and antisocial behavior outcomes as well as knowledge of emotions. Five moderators were explored, including (a) program saturation, (b) dependent variable source, (c) grade range, (d) metro area, and (e) geographical location. A combined total of 18,847 participants were included in the analysis of 27 studies. Results of the current study indicate that Second Step’s impact on students’ knowledge and attitudes of violence and violence prevention is much stronger than on increasing prosocial behavior or reducing antisocial behavior.
Keywords: dept.csp

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Implementing the developmental school counseling core curriculum in the classroom - Perusse, R.; Parzych, Jennifer L.; Erford, Bradley T. (Transforming the School Counseling Profession, 2018)
Transforming the way thousands of professional school counselors approach their work with students Transforming the School Counseling Profession demonstrates how to effectively implement systemic, data-driven school counseling programs.This clearly written text presents the profession in easy-to-understand language, and is illustrated with numerous applied examples, case studies, and vignettes. The 5th Edition has been updated to include all of the latest CACREP, ASCA, and ACA standards. It also now includes the DSM-5. Coverage of cultural competence has been expanded throughout the book. Also available with MyLab Counseling MyLab is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. MyLab Counseling organizes all assignments around essential learning outcomes and the CACREP standards–enabling easy course alignment and reporting. Note: You are purchasing a standalone product; MyLab Counseling does not come packaged with this content. Students, if interested in purchasing this title with MyLab Counseling, ask your instructor to confirm the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information. If you would like to purchase both the physical text and MyLab Counseling, search for: 0134669843 / 9780134669847 Transforming the School Counseling Profession plus MyLab Counseling with Enhanced Pearson eText -- Access Card Package Package consists of:       0134610598 / 9780134610597 Transforming the School Counseling Profession 0134642651 / 9780134642659 MyLab Counseling with Enhanced Pearson eText -- Access Card -- for Transforming the School Counseling Profession
Keywords: dept.csp

Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found